Location-Based Services - Hoi, Huynh Tan; Truong, Le Vu (ABC Journal of Advanced Research, 2019)
In the current information technology trend, GIS (Geographic Information Systems) and GPS (Global Positioning Systems) are potential systems providing convenient, valuable services. They are a fundamental base in location-based services (LBS). LBS is an object positioning and monitoring system with a major combination of advanced technologies such as mobile communications, GPS technology, GIS and the Internet. The article consists of two sections in which the overview of the LBS system is presented first, followed by the introduction of the LBS system structure used to build the VTS - Vehicle Tracking System at Dong A Bank.